The impact of maternal obesity on intra-partum events during pregnancy: a retrospective study at Puducherry - A., Ulagammal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Women with excessive weight at the time of conception are prone to a wide spectrum of adverse pregnancy outcomes including major postpartum haemorrhage, increased caesarean section rates, increased operational vaginal deliveries and higher risks of maternal hypertension, gestational diabetes and fetal death. Methods: This retrospective case-control study was conducted at a tertiary care hospital in Ariyur, Puducherry by comparing 100 obese women (cases) with 100 Non-obese, normal weighted women (controls) in terms their intra-partum pregnancy events and outcomes. Results: Obese women (42%) had an increased risk of having a caesarean section (OR 2.57, 95% CI 1.31-5.1) when compared to the controls (22%). Instrumental delivery rate was significantly higher (p=0.02) in the study group (24%) compared to 11% in the control group (OR 2.56, 95% CI 1.1-6.1). Postpartum haemorrhage (>500 ml) encountered during vaginal deliveries was 32% in the obese group which was significantly higher (p<0.001) when compared with 9% in the control group (OR 4.76, 95% CI 2-12). Conclusions: Obese women had increased incidence of difficult intra-partum events like increased blood loss and post-partum haemorrhage, increased requirement of oxytocin augmentation, higher rates of caesarean and instrumental deliveries, when compared to non-obese women.